(untitled) (The Conference Hub, 2025)
This article explores the spiritual, intellectual, and historical dimensions of the relationship between Shams-i Tabrizi and Jalaluddin Rumi (Mevlana), emphasizing how their meeting marked a turning point in Rumi’s life – leading to a spiritual transformation and deep mystical awakening.